The Improvement of a Thai Organic Rice Supply Chain: A Case Study of a Community Enterprise - Prasertwattanakul, Yaniga; Ongkunaruk, Pornthipa (KnE Life Sciences, 2016)
The demand for organic product has been increasing for decades due to consumer consciousness for health and environment. In Thailand, the volume of organic rice production is increasing, especially for the community enterprises. Our objectives are to explore the supply chain of a community enterprise in Uthai Thani, to analyze the business process and identify the problems and to provide the recommendation for an efficiency improvement. Then, we conduct an in-depth interview to gain better understanding of farmer and the community enterprise. Next, the business process analysis is analyzed using Integration Definition for Function Modeling (IDEF0). For farmers and the community enterprise, the key performance indicators are productivity, cost and quality. Then, the proper controls and mechanisms are proposed. These could be the direction for further development to enhance organic rice supply chain management for Thai producers especially smallholders to penetrate the international and domestic markets. Keywords: Business Process Analysis; Community Enterprise; IDEF0; Organic Rice; Supply Chain Management